When do service suppliers leave their platform?—The role of friendships - Oliver Rossmannek (Review of Managerial Science, 2021)
Platform organizations connect suppliers with customers. A key success factor for these organizations is the maintenance of a stable base of loyal suppliers. Interpersonal relationships (i.e., friendships) seem to be an ideal measure of suppliers' loyalty, as the literature generally indicates that friendships within organizations decrease turnover intention. However, platforms are not fully comparable to traditional organizations, and the correlation between friendships and suppliers' turnover intention is more complicated for platforms. To demonstrate that, this study analyzed a unique dataset from the music industry. The sample included 101 techno DJs (i.e., service suppliers) from 61 booking agencies (i.e., service platforms). The findings show that service suppliers' turnover intention is considerably lower when they maintain friendships with the platform's employees. However, friendships with other suppliers who use the same platform do not affect turnover intention. Managers of service platforms could use the results and suggestions of this paper to adapt their management practices to better suit their service suppliers.
Keywords: M54; 650; Platforms; Service suppliers; Turnover; Friendships; DJs; Booking agencies